PHARMACODYNAMIC AND PHARMACOKINETIC CONSIDERATIONS IN THE CO-ADMINISTRATION OF NUTRACEUTICALS AND PHARMACEUTICALS (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The co-administration of nutraceuticals and pharmaceuticals presents significant challenges due to potential pharmacodynamic and pharmacokinetic interactions. Pharmacodynamically, nutraceuticals can either enhance or inhibit the therapeutic effects of drugs, leading to synergistic, additive, or antagonistic outcomes. For example, omega-3 fatty acids may potentiate the effects of antihypertensive drugs, while high-dose vitamin C might reduce the efficacy of certain cancer therapies. Pharmacokinetically, nutraceuticals can alter drug absorption, metabolism, and excretion, thereby influencing drug plasma concentrations. Notable examples include grapefruit juice increasing drug bioavailability by inhibiting CYP3A4 enzymes, and St. John’s Wort reducing drug effectiveness by inducing the same enzymes. These interactions underscore the importance of personalized medicine, where factors such as genetics, age, and overall health status must be considered to optimize therapeutic outcomes and minimize risks. As the popularity of nutraceuticals continues to grow, healthcare professionals must proactively manage these interactions through patient education and a thorough understanding of the underlying mechanisms. This paper provides a comprehensive overview of the pharmacodynamic and pharmacokinetic considerations in the co-administration of nutraceuticals and pharmaceuticals, highlighting the need for further research and evidence-based guidelines to ensure safe and effective use in clinical practice.